Tumor cells PD-L1 expression as a favorable prognosis factor in nasopharyngeal carcinoma patients with pre-existing intratumor-infiltrating lymphocytes - Zhu, Qian (Oncoimmunology, 2017)
Programmed death ligand 1 (PD-L1) expression represents a mechanism of immune escape by inhibiting T cell immunity. This study systematically evaluated the expression of PD-L1, spatial distribution of CD3(+) immune cells and the relationship of both factors to survival in nasopharyngeal carcinoma (NPC) patients. A total of 209 NPC patients treated between 1991 and 2000 were included. Pairs of TMAs were immunohistochemically stained with PD-L1 and CD3. Survival analysis was evaluated according to PD-L1 status and the spatial distribution of CD3(+) immune cells in the primary lesion microenvironment. PD-L1 staining was observed on tumor cells and tumor-infiltrating immune cells (TILs); however, PD-L1-positive immune cells were more common (98/209) than PD-L1-positive tumor cells (68/209). Limited numbers of intra-tumoral CD3(+) T cells (median number: 20) were detected. Patients with higher CD3(+) T cell infiltration, both intratumorally and peritumorally, had higher PD-L1 expression on tumor cells (both p < 0.001) and immune cells (p = 0.002 and p < 0.001, respectively). Increasing intratumoral CD3 infiltration was correlated with increased overall survival (OS) (p = 0.008) and disease-free survival (DFS) (p = 0.003). Nevertheless, patients with low levels of peritumoral TILs showed superior OS (p = 0.557) and DFS to those with higher levels of peritumoral TILs (p = 0.671). Moreover, type classification based on intratumoral CD3 infiltration and tumor cell PD-L1 expression was an independent prognostic factor for NPC patients. PD-L1 expression on tumor cells is a favorable prognosis factor in NPC patients with pre-existing intratumor-infiltrating lymphocytes.